Application Research of Fuzzy Theory in PE Teaching Evaluation - Chen Ying; Ji Liu; Liu Qin (Institute of Advanced Engineering and Science, 2013)
Comprehensive evaluation of PE teaching is always one the of difficulties of teaching management for universities; This paper, on the basis of analyzing the fuzzy features of teaching evaluation, puts forward fuzzy evaluation model of PE teaching. The model first discards the defects of traditional evaluation methods which always neglect the specific characteristics of PE teaching, instead, takes teaching objectives and results as orientation, designs new comprehensive evaluation indicators for PE teaching; Second, analytic hierarchy process and multivariate fuzzy evaluation method are used to build the evaluation model for PE teaching through building membership function and comprehensive evaluation matrix of fuzzy comprehensive evaluation; Finally, the model is realized by the data from three universities to carry out comprehensive evaluation on PE course and the experimental results indicate that the presented model has satisfied application results in evaluation accuracy and time consumption compared with traditional methods. DOI: http://dx.doi.org/10.11591/telkomnika.v11i9.3259